Public Finance: Present Sphere and Defense Expenditure in Nepal - Poudel, Chandra Kanta (Socio-Economic Development Panorama, 2008)
The present harmonious situation of Nepal demands for breaking down the old strategy of defense economics of Nepal and setting a new one. It should give economic development top priority, which may, consequently, help make the country stronger. The percentage of defense expenditure to GDP and its share of total expenditure of government have significantly increased in the last decade of conflict. Cutting down the defense expenditure may help reallocate the resources for social sector such as education and capital formation. And the new strategy should not cause the reduction of safe and peaceful environment of the motherland and be set addressing the peace process with Maoists. Socio-Economic Development Panorama Vol.1(1) 2007 pp.113-124